Diseño de plan de negocio para la creación de la empresa Pilar Alvargonzález (2016)
For the degree project the selection of the area of entrepreneurship was carried out in order to create an exclusive feminine footwear brand called Pilar Alvargonzález (PA), in this project it is intended to elaborate the whole business plan of the brand previously mentioned for the creation of Is a company in charge of designing and marketing footwear for women, which has the future in mind to be able to export and be recognized internationally.